Management Assistance in the Aluminum Home Industry - Marsuhin Marsuhin (Trescode Green Organization, 2024)
Management assistance activities in the aluminum home industry aim to help business management to be more effective and efficient through the application of socialization, discussion, and training methods. This method is used to improve business actors' understanding of production, financial, and marketing management which are still challenges for them. The socialization stage is carried out through the introduction of basic business management concepts, followed by interactive discussions to explore specific problems faced by the industry. Furthermore, practical training is provided to introduce product packaging techniques, simple financial records, and marketing strategies through social media. The results of this activity show a significant increase in business actors' understanding of managing their businesses. Participants were able to implement more attractive packaging techniques, make financial records more structured, and start utilizing digital media to expand the market. This activity not only provides short-term solutions, but also equips business actors with management skills that can be applied sustainably. Thus, this assistance has succeeded in increasing the competitiveness of the aluminum home industry and encouraging more sustainable business growth.